Formation of the Relationship between the Exchange Rate and the Investment Yield of Pension Assets in Kazakhstan: Causes and Consequences - V. Yu. Dodonov (Финансы: теория и практика, 2023)
The efficiency of pension asset management, reflected in their performance, determines the stability of the funded pension system of Kazakhstan, and also has the potential to significantly affect the budget process, since the state guarantees recipients a positive real return on their pension savings and compensates from the budget for losses incurred during periods when inflation exceeds the nominal rate of return. The need to ensure a positive real return on pension assets managed by the National Bank of Kazakhstan determines not only the high relevance of the issue of investment management itself, but also other aspects that affect the return, including changes in the exchange rate of the Kazakhstani tenge. The subject of the article is the impact of the tenge exchange rate on the profitability of pension assets, which can be very significant, since it forms one of the main components of investment income — income from foreign currency revaluation. This influence can also act as a factor in the formation of the tenge exchange rate during periods when the real return of pension assets decreases due to the negative situation in the financial markets and high inflation, and this thesis reflects the scientific novelty of the article. The assessment of the hypothesis about the formation of the relationship between the exchange rate of the Kazakhstani currency and the investment yield of pension assets is the aim of this work, and the identification of the main causes and consequences of this phenomenon is its task. Comparative and correlation analysis of indicators of investment return of pension assets, changes in the exchange rate of the Kazakhstani currency, parameters of the external sector and others were used as research methods. The results of the analysis confirm the existence of a relationship between the indicators of profitability of pension assets and the tenge exchange rate, and allow us draw the conclusion that this profitability has an indirect impact on the formation of the Kazakhstani currency exchange rate over the past few years, which has been characterized by non-standard dynamics in the context of a significant improvement in the external economic environment.